Pregnancy after lung transplant: Case Report. Issue 4 (December 2015) - Divithotawela, Chandima; Chambers, Daniel; Hopkins, Peter
Improved survival now means that more women with lung transplants than ever before, many of whom have a diagnosis of cystic fibrosis, may be able to consider pregnancy. However, lung transplant recipients have increased risk of maternal and neonatal complications associated with pregnancy [1 ]. These pregnancies should be planned in advance and closely monitored. Pregnancy should be avoided for a minimum of 1–2 years after transplant to minimise episodes of acute rejection and achieve the lowest possible doses of immunosuppressive drugs. Immunosuppression with mycophenolate mofetil and mammalian target of rapamycin (mTOR) inhibitors should be avoided because of teratogenic effects. Immunosuppression based on prednisolone, azathioprine and calcineurin inhibitors should be established before conception. Vaginal delivery is encouraged due to the lower risk of infection and adverse events of general anaesthesia that may occur with caesarean delivery. Breast feeding is discouraged because of the risk of infant exposure to immunosuppressive drugs via breast milk, though remain a controversial recommendation. We present a patient who had successful pregnancy after lung transplant for cystic fibrosis. Improved survival now means that more women with lung transplants than ever before may be able to consider #pregnancy http://ow.ly/Ute17